Can high-lipid concentrates offset the high enteric methane production caused by high-forage diets fed to lactating dairy cows? - N. Ayanfe; I. Tapio; S. Ahvenjärvi; M. Rinne; A. Sairanen; A.R. Bayat (Journal of Dairy Science, 2025)
ABSTRACT: Ruminants have the ability to utilize forages to produce high-quality products for human consumption. However, feeding high-forage diets can increase enteric methane (CH4) production. Therefore, this study examined the viability of using a high-ether extract concentrate as a compensatory strategy to mitigate elevated CH4 production, while assessing effects on performance, digestibility, energy utilization, and ruminal and fecal microbiota. Four multiparous Nordic Red dairy cows in early lactation (averaging 61 ± 16.4 DIM) were randomly assigned to a 4 × 4 Latin square design in a 2 × 2 factorial arrangement of dietary treatments. There were four 21-d experimental periods, each consisting of a 16-d adaptation and a 5-d sampling period in metabolic chambers. The diets comprised TMR based on grass silage with a forage-to-concentrate (FC) ratio of 70:30 (high-forage; HF) or 50:50 (low-forage; LF) mixed with either a low-ether extract concentrate (LEE) containing rapeseed meal and barley or a high-ether extract concentrate (HEE) containing rapeseed cake and oats. Ether extract concentrations were 36, 48, 32, and 53 g/kg of DM for HF-LEE, HF-HEE, LF-LEE, and LF-HEE, respectively. The DMI was 3.2 kg/d lower in cows fed HF compared with LF diets, with no effect of concentrate type. Digestibility of NDF and OM was significantly lower in the LF-HEE diet compared with the other diets. Additionally, HF diets reduced milk yield, which further declined with HEE supplementation. The LF and HF diets had similar daily CH4 production (grams/day), and CH4 yield (grams/kilogram of DMI) was greater for HF compared with LF diets. Ether extract supplementation was more effective in reducing CH4 yield in the HF than the LF diet (7.1 vs. 4.2 g CH4/kg of DMI per each kilogram added ether extract). Methane intensity was the lowest in the LF-HEE diet; however, HF-HEE diet reduced CH4 intensity (grams/kilogram of ECM) by 5.5% compared with HF-LEE, matching that observed with LF-LEE diet. Significant changes in rumen bacterial, archaeal, and fungal abundances were induced by the dietary FC ratio, and rumen protozoa and fecal fungi abundances were affected more by concentrate type. In conclusion, incorporating HEE in an HF diet reduced CH4 intensity to levels comparable to those achieved with LEE in LF diets. These findings suggest that supplementing HF diets with HEE concentrates could be a practical and cost-effective strategy for sustainable dairy production.